Land and livelihood strategies to improve nutrition in rural India: a mixed methods study. - S, Krishnan.; H, Harris-Fry.; A, Prost.; S, Rath.; E, Allen.; S, Gouda.; S, Mohanty.; S, Pradhan.; NK, Mishra.; R, Pradhan.; S, Kadiyala. (Tufts University. Tisch Library., 2019)
This presentation was from 6th Annual scientific Symposium in Nepal.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy